Interactional Metadiscourse Markers. A Survey Study on Iranian M.A. TEFL Theses - Abbaszadeh, Ebrahim; Hosseini, Seyedeh Azam; Aghajani, Mojtaba (European Journal of Sustainable Development, 2019)
The present study examined the differences in the use, type, and frequency of interactional metadiscourse markers in theses written by M.A. TEFL graduates including 10 males and 10 females from Malayer University. The selected corpus was analyzed using Hyland’s in 2005 interactional model of metadiscourse. The data were explored through a manual corpus analysis method using Adobe PDF reader software. Moreover, a Chi-Square statistical measure was run to examine whether there were any significant differences in the use of metadiscourse markers in different thesis chapters and across different genders. The results revealed that although there were some subtle differences in the frequency and types of these metadiscourse markers, there was no statistically significant difference between two genders in the use of interactional metadiscourse markers. Besides, it was concluded that there was a significant relationship between the chapters of theses and the use of metadiscourse markers. The findings of this study render some pedagogical implications for writing courses at M.A. and PhD levels in the realms of TEFL and ESP. Keywords: Metadiscourse, Interactional markers, Applied Linguistics, M.A. thesis, Gender